Effects of Acute Tryptophan Depletion on Repetitive Behavior in Laying Hens - Birkl, Patrick; Chow, Jacqueline; McBride, Peter; Kjaer, Joergen B.; Kunze, Wolfgang; Forsythe, Paul; Harlander-Matauschek, Alexandra (Frontiers in Veterinary Science, 2019)
Repetitive pecking at the feather cover of other birds (FP) is one of the most important welfare problems in domestic birds. It is not only characterized by motor symptoms, but also by an innate vulnerability of the serotonergic system. Moreover, the serotonergic system influences cognitive function. Acute tryptophan depletion (ATD) is a widely used method for studying serotonergic function in mammals and has been recently validated in birds. However, a tryptophan-deficient amino acid mixture has never been tested on groups of birds to impact their social behavior, including repetitive feather pecking, nor has it been given to potentially impact their cognition and motor performance. One hundred and sixty White Leghorn laying hens consisting of two genetic lines divergently selected to perform high (H) or low (L) levels of FP, and an unselected control line (UC), were kept in 10 groups consisting of 4 H, 3 L, and 9 UC genotypes. In a counterbalanced order, half of the groups were first subjected to an ATD treatment, while the other half were first given a balanced control (BC) treatment, and vice versa, after which their feather pecking behavior was observed. The effect of ATD/BC on repetitive pecking, motor performance, and cognition was investigated in a 5-s delayed reward task in an operant chamber with 10 phenotypic feather peckers, 10 recipients of feather pecking, and 10 bystanders (who neither performed nor received feather pecks). ATD given to groups of birds induced gentle, repetitive feather pecking in all genotypes. Following ATD, phenotypic feather peckers performed more poorly during the delayed reward task, as seen by their higher number of repetitive, non-rewarded key, and non-key pecks in the operant chamber. In conclusion, ATD impacted the hens' social behavior by increasing the number of repetitive gentle feather pecks at conspecifics. Furthermore, feather peckers were more likely to peck while waiting for a reward after ATD, suggesting a role for the serotonergic system on cognition in these birds.